2022
DOI: 10.3233/mnm-211521
|View full text |Cite
|
Sign up to set email alerts
|

The difference in the dietary inflammatory index, functional food, and antioxidants intake between COVID -19 patients and healthy persons

Abstract: BACKGROUND: The healthy diet is important to maintain immunity against infection. This study aimed to assess and compare the consumption of functional foods, some antioxidants, and dietary inflammatory index between Iranian COVID-19 patients and healthy persons. METHODS: This case-control study was conducted between 1000 (500 cases and 500 controls) adults aged 18–65years in Iran, that were sampling based on the snowball method and their information was collected electronically. The dietary intake was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The last ecological study available was based on the evaluation of selenium (and other nutrients) intake, from 138 food items, by means of a Food Frequency Questionnaire (FFQ) that was submitted to 500 WhatsApp-recruited Iranians with a history of COVID-19 diagnosis but not treated in hospital, and to as many non-COVID-19 Iranians [ 52 ]. The authors reported a significantly lower selenium intake in COVID-19 individuals and claim that “an increase of one unite in selenium consumption reduced the risk of COVID-19 incidence by 91%”.…”
Section: Resultsmentioning
confidence: 99%
“…The last ecological study available was based on the evaluation of selenium (and other nutrients) intake, from 138 food items, by means of a Food Frequency Questionnaire (FFQ) that was submitted to 500 WhatsApp-recruited Iranians with a history of COVID-19 diagnosis but not treated in hospital, and to as many non-COVID-19 Iranians [ 52 ]. The authors reported a significantly lower selenium intake in COVID-19 individuals and claim that “an increase of one unite in selenium consumption reduced the risk of COVID-19 incidence by 91%”.…”
Section: Resultsmentioning
confidence: 99%
“…Although diet alone is not sufficient for the prevention of any virus infection, adequate nutrition is viewed as one of the best complementary approaches for controlling many types of infections, including SARS-CoV-2. Optimal dietary intake of macro-and micronutrients and other bioactive constituents may affect the immune system and thus strengthen the protection against influenzalike illnesses such as COVID-19 disease (1,11,17,31). Unfortunately, the pandemic has had a significant impact on nutritional habits, yet dietary changes have manifested differently and to various extents among men and women as well as in people with distinct socioeconomic status (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Bousquet et al ( 26 ) pointed out that besides many factors such as trained immunity of the population and public hygiene, diet had an important role in the extension and severity of COVID-19. In fact, Mohajeri et al ( 27 ) demonstrated that dietary intake of antioxidants such as vitamin D, vitamin C, vitamin E, Zn, Se, and some functional foods such as onion, garlic, and oat was significantly higher in healthy cohorts than in COVID-19 patients. Functional foods maintain gut health via the modulation of the gut microbiota, which has enormous beneficial effects ( 28 ), while antioxidant supplements may help to boost the immune system, reduce oxidative stress and inflammation, and prevent the progression of COVID-19 disease severity ( 27 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Mohajeri et al ( 27 ) demonstrated that dietary intake of antioxidants such as vitamin D, vitamin C, vitamin E, Zn, Se, and some functional foods such as onion, garlic, and oat was significantly higher in healthy cohorts than in COVID-19 patients. Functional foods maintain gut health via the modulation of the gut microbiota, which has enormous beneficial effects ( 28 ), while antioxidant supplements may help to boost the immune system, reduce oxidative stress and inflammation, and prevent the progression of COVID-19 disease severity ( 27 , 29 ). Ebrahimzade et al ( 30 ) indicated that, compared with unhealthy or traditional dietary patterns, healthy dietary patterns can decrease the C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) levels, as well as negative COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 99%